AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA, TRANSPARANSI, PARTISIPASI MASYARAKAT, KELEMBAGAAN DAN KEBIJAKAN DESA TERHADAP KESEJAHTERAAN - Ernawan Septia Putri Ussholehah; Anggoro, Rusmawan Wahyu (LPPM STIE YKPN Yogyakarta, 2024)
Village Fund Allocation (ADD) is a fund sourced from the central and regional financial balance funds with proportional distribution distributed by the Regency/City Government for Villages. The village fund allocation program, if carried out properly, has a very large and effective influence on the welfare of the community. This study aims to determine the influence of accountability, transparency, institutions, policies and community participation in ADD on welfare. Thi quantitative research using primary data obtained through the distribution of questionnaires with a total of 181 respondents. Data analysis uses multiple linear regression processed with the SPSS program. The results of the study show that the variables of ADD management accountability and transparency have no effect on community welfare. The welfare of village communities is influenced by institutions, village policies and community participation.